A putative pathway of glyconeogenesis in skeletal muscle. Issue 2 (February 1981) - Odedra, Bhanu R.; Palmer, T. Norman
Abstract : Evidence is presented in support of a pathway in skeletal muscle of glyconeogenesis (glycogen biosynthesis de novo) from L-glutamate and related amino acids involving the enzyme phosphoenolpyruvate carboxykinase (PEP CK). In the rat hemidiaphragm in vitro, not only did L-[U- 14 C]glutamate exert a glycogen-sparing action, but 14 C-label was incorporated into glycogen. The incorporation is thought not to be simply via label randomization and was decreased by factors that increased glycolysis or pyruvate oxidation. 3-Mercaptopicolinate and amino-oxyacetate, specific inhibitors of PEP CK and aminotransferase-type enzymes, respectively, decreased 14 C-incorporation from L-[U- 14 C]glutamate into glycogen. No quantitative determination of apparent glyconeogenic flux was made, and it remains to be established whether glyconeogenesis via PEP CK and/or via PEP CK coupled with 'malic' enzyme (or pyruvate carboxylase) is functionally important in skeletal muscle.